Principals' leadership styles and its impact on teachers' performance at college level - Sarwar, Uzma; Tariq, Rameez; Yong, Qi Zhan (Frontiers in Psychology, 2022)
In this study, we examined the impact of principals' leadership style on the performance of teachers at the college level. For this purpose, we collect data from 300 college teachers via a random sampling approach. A self-administrated questionnaire (five-point Likert Scale) was used to collect data. For detecting relationships and differences among the opinions of the study's participants, correlation and the t-test were used. This study has revealed that the majority of college principals practice a democratic style of leadership at a higher level, Laissez-faire at a moderate level, and autocratic at a low level in their colleges. Moreover, it has been also revealed that when principals increase the use of a democratic leadership style, teacher performance may progress as well. The findings revealed that principals’ leadership style had a positive impact on the performance of teachers. The study exposed a strong statistically positive relationship between college principals’ leadership style and teacher performance. Thus, the results of this study suggest that college principals’ should adopt the leadership style according to the level of teachers. The leadership style should be changed with specific situations in the colleges.